2003
DOI: 10.1063/1.1543237
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the surface roughness evolution during hydrogenated amorphous silicon film growth

Abstract: The scaling behavior of the surface morphology of hydrogenated amorphous silicon deposited from a SiH3 dominated plasma has been studied using atomic force microscopy and in situ ellipsometry. The observed substrate temperature dependence of growth exponent β reflects a crossover behavior from random deposition at 100 °C to a surface diffusion controlled smoothening around 250 °C to full surface relaxation around 500 °C. This crossover behavior has been reproduced by Monte Carlo simulations assuming a site dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 19 publications
(24 reference statements)
2
23
0
Order By: Relevance
“…Smets and co-workers studied the scaling behavior of the growth surface morphology of a-Si:H films and derived an activation energy barrier of 1:0 eV for the smoothening mechanism [8]. However, Kondo and co-workers performed an ex situ study of a-Si:H surface morphology over the range 50 C < T < 450 C, and indicated a weakly activated smoothening process [10], in agreement with the results of Ref.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…Smets and co-workers studied the scaling behavior of the growth surface morphology of a-Si:H films and derived an activation energy barrier of 1:0 eV for the smoothening mechanism [8]. However, Kondo and co-workers performed an ex situ study of a-Si:H surface morphology over the range 50 C < T < 450 C, and indicated a weakly activated smoothening process [10], in agreement with the results of Ref.…”
supporting
confidence: 70%
“…The T dependence of the surface roughening evolution of a-Si:H films has been analyzed in several experiments, under conditions where the dominant deposition precursor is the SiH 3 radical [7][8][9][10][11]. Smets and co-workers studied the scaling behavior of the growth surface morphology of a-Si:H films and derived an activation energy barrier of 1:0 eV for the smoothening mechanism [8].…”
mentioning
confidence: 99%
See 3 more Smart Citations